Determination of free amino acids in whole-fat Turkish White Brined Cheese produced by animal and microbial milk-clotting enzymes with and without the addition of starter culture - Ufuk Eren-Vapur; Tulay Ozcan (Mljekarstvo)
Coagulating enzymes are essential ingredients for the production of different cheese varieties. The objective of this research was to summarize the effect of rennet type (calf rennet and microbial rennet from Rhizomucor miehei) and starter culture on the sensory properties and free amino acids (FAA) release during the ripening of Turkish White brined cheese. The concentrations of FAA and sensory properties were similar for cheeses made with both types of coagulant and starter culture. Aminoacids Phe, Leu - Ile, Gln, Val, Pro and Ala were the principal FAAs in the White brined cheeses at all stages of ripening.